1997
DOI: 10.1093/emboj/16.23.7032
|View full text |Cite
|
Sign up to set email alerts
|

Signal characteristics of G protein-transactivated EGF receptor

Abstract: The epidermal growth factor receptor (EGFR) tyrosine kinase recently was identified as providing a link to mitogen-activated protein kinase (MAPK) in response to G protein-coupled receptor (GPCR) agonists in Rat-1 fibroblasts. This cross-talk pathway is also established in other cell types such as HaCaT keratinocytes, primary mouse astrocytes and COS-7 cells. Transient expression of either G q -or G i -coupled receptors in COS-7 cells allowed GPCR agonist-induced EGFR transactivation, and lysophosphatidic acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

36
493
2
1

Year Published

1998
1998
2009
2009

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 615 publications
(532 citation statements)
references
References 68 publications
36
493
2
1
Order By: Relevance
“…In the present study, we Stimulation of EGF receptor is known to induce cell proliferation [2,20]. This is associated with ERK activation at 5-60 min following the stimulation of EGF receptor [21,22], that is occasionally accompanied by JNK activation [23][24][25]. In SVHK cells, EGF activated ERK and JNK, that were associated with cell proliferation.…”
Section: Discussionmentioning
confidence: 89%
“…In the present study, we Stimulation of EGF receptor is known to induce cell proliferation [2,20]. This is associated with ERK activation at 5-60 min following the stimulation of EGF receptor [21,22], that is occasionally accompanied by JNK activation [23][24][25]. In SVHK cells, EGF activated ERK and JNK, that were associated with cell proliferation.…”
Section: Discussionmentioning
confidence: 89%
“…Whole cell lysates from FHL-124 cells were prepared using Daub lysis buffer (Daub et al, 1997) supplemented with 1 mM phenylmethylsulfonyl fluoride (PMSF) and 10 mg/ml aprotinin for 20 min on ice and centrifuged at 13 000 rpm for 10 min. The protein concentration in the supernatant was determined using the bicinchoninic acid protein assay (Pierce, Rockford, IL).…”
Section: Western Blot Analysismentioning
confidence: 99%
“…Using NT as a prototype neuropeptide, and knowing that the NT receptor is a GPCR (Seethalakshmi et al, 1997), we hypothesized that NT secreted by NE-like cells can act upon prostate cancer cells to transactivate the EGFR as described in the Introduction (Daub et al, 1996(Daub et al, , 1997Prenzel et al, 1999). To test this hypothesis, PC3 cells were pre-incubated with SR48692, a potent and selective non-peptide antagonist for the neurotensin receptor (NTR) (Gully et al, 1993) with specificity for NTR1 (Labbe-Jullie et al, 1998).…”
Section: Nt-induced Transactivation Of the Egfrmentioning
confidence: 99%
“…Numerous, recent reports have shown that transactivation of the epidermal growth factor (EGF) receptor (EGFR) is critical for the mitogenic activity of multiple GPCR agonists (Daub et al, 1996(Daub et al, , 1997Prenzel et al, 1999;Madarame et al, 2003;Xiao et al, 2003;Zhao et al, 2004) and that EGFR transactivation requires metalloproteinase (MMP) cleavage of pro-heparin-binding EGF-like growth factor (pro-HB-EGF) into HB-EGF, which is released from the cell surface to bind the EGFR in an autocrine or paracrine manner (Prenzel et al, 1999;Madarame et al, 2003;Santiskulvong and Rozengurt, 2003;Yano et al, 2004;Zhao et al, 2004;Hassan and Carraway, 2006). However, the detailed signaling events following EGFR transactivation that are required for mitogenic activation are not fully understood, particularly in prostate cancer cells.…”
Section: Introductionmentioning
confidence: 99%